Differential effect of COMT gene methylation on the prefrontal connectivity in subjects with depression versus healthy subjects. (15th July 2018) - Na, Kyoung-Sae; Won, Eunsoo; Kang, June; Kim, Aram; Choi, Sunyoung; Tae, Woo-Suk; Kim, Yong-Ku; Lee, Min-Soo; Joe, Sook-Haeng; Ham, Byung-Joo
Abstract: Expression of the catechol-O-methyl transferase (COMT) gene mainly determines prefrontal dopaminergic availability. Deficient prefrontal dopaminergic activity leads to loss of interest, energy, and motivation, which are core symptoms of depression. Given the role of stress-environmental interactions in major depressive disorder (MDD), we investigated the impact of COMT gene methylation status on prefrontal connectivity. We measured COMT gene methylation and polymorphisms (Val158Met) at the rs4468 locus in peripheral blood samples of healthy controls (n = 90) and patients with MDD (n = 90). We used diffusion tensor imaging to calculate the fractional anisotropy (FA) and radial diffusivity (RD) of the white matter tracts related to prefrontal cortex. Finally, we examined the effects of COMT gene methylation on the white matter connectivity in patients with MDD. The FA and RD values in the prefrontal white matter tracts of patients with MDD were positively and negatively associated with COMT gene methylation, respectively. In the control group, on the other hand, the association between white matter connectivity and COMT gene methylation showed opposite pattern to those of MDD. COMT gene methylation has a substantial effect on the prefrontal connectivity in patients with MDD. Moreover, COMT gene methylation and prefrontal connectivity showed opposite relationships in patients and controls. Thus, stress-related alterations in dopaminergic neurotransmission have a differential effect on white matter connectivity according to the microenvironment in the brain. Highlights: COMT gene methylation was lower in patients with depression than in healthy control individuals. The FA (and RD) of the white matter tracts of the PFC were lower (and higher) in patients than those in controls. The COMT gene methylation had opposite relationships with white matter connectivity in the two groups.